The History and Future of Private Education in the United States - Glenn, Charles L. (Catholic Education: A Journal of Inquiry and Practice, 1998)
In the early Republic, no simple distinction between public and private schools existed. With the advent of the common school, a system of government-sponsored schools emerged. Hostility to nonpublic schools, especially Catholic ones, developed because of the fear that they would undermine the foundation of civil and political order. This hostility has historically been expressed through regulation and denial of funding. Currently, private schools are experiencing a more favorable public attitude because of a widespread disillusionment with public schools. The future of private schools depends on how faithfully they express a distinctive and worthy character to their institutions.